2014
DOI: 10.1200/jco.2014.55.3925
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial to Test Accelerated Versus Standard Fractionation in Combination With Concurrent Cisplatin for Head and Neck Carcinomas in the Radiation Therapy Oncology Group 0129 Trial: Long-Term Report of Efficacy and Toxicity

Abstract: When combined with cisplatin, AFX-C neither improved outcome nor increased late toxicity in patients with LA-HNC. Long-term high survival rates in p16-positive patients with oropharyngeal cancer support the ongoing efforts to explore deintensification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
267
5
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(298 citation statements)
references
References 28 publications
16
267
5
10
Order By: Relevance
“…Based on the review of the results of clinical trials reported until the early 2000s, the study by Ang (10) suggested that a cumulative cisplatin dose of 200 mg/m 2 would be the threshold for patients to yield a beneficial antitumor effect from CCRT regardless of the schedule. Previous studies also suggest that a cumulative dose of 200 mg/m 2 is the threshold to experience a benefit from CCRT (11,12), and certain clinical trials set a total dose of 200 mg/m 2 in their control group (9,13). Based on these findings, the present study used the cumulative dose of 200 mg/m 2 as the target dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the review of the results of clinical trials reported until the early 2000s, the study by Ang (10) suggested that a cumulative cisplatin dose of 200 mg/m 2 would be the threshold for patients to yield a beneficial antitumor effect from CCRT regardless of the schedule. Previous studies also suggest that a cumulative dose of 200 mg/m 2 is the threshold to experience a benefit from CCRT (11,12), and certain clinical trials set a total dose of 200 mg/m 2 in their control group (9,13). Based on these findings, the present study used the cumulative dose of 200 mg/m 2 as the target dose.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive factors of high-dose cisplatin tolerance. cycles are correlated with the prognoses of HNSCC patients receiving CCRT (9). Based on the review of the results of clinical trials reported until the early 2000s, the study by Ang (10) suggested that a cumulative cisplatin dose of 200 mg/m 2 would be the threshold for patients to yield a beneficial antitumor effect from CCRT regardless of the schedule.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with locoregionally advanced disease, multimodality therapy with chemotherapy and radiotherapy improves organ preservation and survival, although longterm disease-free survival is often below 50% (1)(2)(3)(4)(5). Patients with tumors negative for human papillomavirus (HPV) have particularly worse outcomes, with 3-year overall survival less than 60% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is a significant correlation between hemoglobin level and tumor oxygenation in HNSCC patients [4]. In addition, the clinical impact of genetic alterations such as HPV/p16 expression on toxicities has been discussed [5,6]. Concurrent radiochemotherapy (RCT) is the standard treatment for patients suffering from locally advanced HNSCC.…”
Section: Introductionmentioning
confidence: 99%